Strategi Guru dalam Mengembangkan Kemandirian Anak Usia Dini di RA Al-Asrafy Asyaman Swakarsa - Hermansyah Hermansyah; Siti Mariah (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
The purpose of this study is to describe what Special Strategies are carried out by teachers in developing the independence of early childhood in group A at Raudhatul Athfal AL-Asrafy Asyaman Swakarsa. And what factors influence the independence of early childhood in group A aged 4-5 years at Raudhatul Athfal AL-Asrafy Asyaman Swakarsa. The type of research used is descriptive qualitative using observation, interview and documentation methods. The data analysis technique uses the concept of Miles and Hubermen, with the steps of data reduction, data presentation, and drawing conclusions. The results of this study indicate that the specific strategies given by teachers in developing the independence of early childhood in group A at Raudhatul Athfal AL-Asrafy Asyaman Swakarsa are 1) Teachers encourage children to carry out their daily activities independently without the help of others, 2) Provide opportunities for children to make their own decisions, 3) provide opportunities for children to play without being accompanied, 4) Give children the opportunity to do something themselves even though they often make mistakes 5) Encourage children to express their feelings and ideas, and 6) Train children to socialize and adapt so that children can learn to face complex social problems. Factors that can influence the independence of early childhood in Raudhatul Athfal AL-Asrafy Asyaman Swakarsa are parenting factors and environmental factors.